Pengaruh Komunikasi Organisasi Terhadap Motivasi Kerja Pegawai PT. Bank Sumut Kc Binjai - Nur, Mutiara Ikhwan; Syafrizaldi, Syafrizaldi (Universitas Medan Area, 2025)
This study aims to determine the effect between organizational communication with work motivation on employees of PT Bank Sumut KC Binjai. This research uses a quantitative approach method. The subjects in this study amounted to 75 employees. The sampling technique used the total sampling method, namely all employees. Data analysis using simple linear regression. The results showed that there was a correlation with 0.551 p 0.000, meaning that there was a significant influence between organizational communication and work motivation in employees. The coefficient of determination of the correlation is r2 = 0.304, meaning that organizational communication makes an effective contribution to work motivation by 30.4% while the rest is determined by other influencing factors not examined in this study. Furthermore, judging from the calculation of organizational communication in this study, the hypothetical mean = 70 empirical mean = 96.51 in the high category. Likewise, Work Motivation in this study is also classified as high from the calculation of the hypothetical mean = 90 empirical mean = 122.77.